A STUDY ON IMPACT OF STRESS ON GRADUATING STUDENTS IN HYDERABAD - Pelleti, Dr Swarupa; Mr Kruthivasa; Gouthami, Ms Vangala; Vasavi, Ms M (The journal of contemporary issues in business and government, 2023)
Stress can be defined as any type of change that causes physical, emotional, or psychological strain. Stress is body’s response to anything that requires attention or action. Everyone experiences stress to some degree. Stress has become a common problem for everyone from teenagers to adults it has taken over lives of people and taken control. Stress is a major problem in today’s world and people have no idea how to deal with this problem. Stress can cause mental health problems and it can make existing problems worst. If any individual experience lots of stress, this might lead to develop a mental health problem like anxiety or depression or a traumatic period of stress might lead to post-traumatic stress disorder (PTSD). The objective of the study is to find causes and consequences of stress among graduating students. The data was collected from BBA, BCom B.Sc. graduating students with the sample of 120 in Hyderabad. The data was analyzed using JASP. The main stressors among the students are identified academics, finances, career, and relationships. Academics followed by Career factors cause more stress in graduating students.